Free to Learn? Education in Australia’s Offshore Immigration Detention Centres - Szurlej, Christina (Revue de l’Université de Moncton, 2017)
Children seeking asylum are among the most vulnerable groups in the world. Arriving in a country of refuge should be synonymous with safety; this is not so in Australia. Unaccompanied children arriving by boat are automatically transferred to and detained in the Regional Processing Centre on the Republic of Nauru with no one to advocate on their behalf of their rights and best interests, including their right to an adequate education. Trapped on the small island and uncertain of their futures, children overwhelmingly expressed despair and helplessness, many turning to self-harm. In 2015, the Australian government awarded the contract for education to Broadspectrum, formerly known as Transfield Services Ltd. – a company implicated in the abuse and neglect of children. Since then, truancy rates have increased due to fears for safety, poor structural conditions in schools, and lack of qualified teachers. Failing to provide access to education thwarts the life chances of youth who are already severely disadvantaged and contravenes Australia’s international human rights obligations.